In-Situ Determination of Buildings’ Thermo- Physical Characteristics - Arash Rasooli (A+BE: Architecture and the Built Environment)
Ever since the introduction of energy conversion systems in the built environment, buildings have become responsible for a considerable share of global energy consumption. Many countries have therefore aimed to invest on buildings’ energy efficiency plans to reduce the depletion rate of the fossil resources and the CO2 emissions associated with them. In this context, accurate determination of building’s thermo-physical characteristics is a necessity in the processes which lead to execution of energy conservation strategies in existing buildings. These characteristics are the essential inputs for buildings’ thermal modelling, quality control, energy audits, and energy labelling, the results of which are determinant for energy renovation decisions and policies. In practice, the values of these parameters are not always available because the current determination methods are time-and-effort-expensive, and consequently rarely used. In accordance with the large deviations observed between the in-lab and in-situ thermal behaviour of building components, a special attention is laid on in-situ methods. This thesis aims at developing and testing different in-situ determination methods and approaches at different levels. Theories, simulations, and experiments, are combined for determination of a number of buildings’ most important thermo-physical characteristics.